Sejarah Dan Dakwah Institusi Pendidikan Tinggi Islam Awam (Ipta) Di Pattani Thailand Selatan - Abdulrasyid Abdulrasyid; Mahsidi Salae; Muhammad Azhar Zailani; Ghazali Darusalam (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2017)
This paper attempts to look at the history of the establishment of an Islamic high institution based on the spirit of mutual understanding, unification, and cooperation in the process of strategic planning of Muslims in Southern Thailand. This paper is also to show that the teachings of Islam and its colleges are comprehensive (syumul) and not all that brought by modernized currents are rejected by Islam. The purpose of this study in addition to analyzing the history of the establishment of Islamic university institutions in Southern Thailand, the author tries to read the history of the establishment of an Islamic higher education institution in Pattani, to impact the history of manifestation and development in the field of Islamic universities that became the basic for the construction of muslims realized in the program and aspect of socio-economic reform of the ummah which is also part of Islamic dakwah. This review will examine the history of Islamic education grow that occurred at the Islamic University of Islamic College Songkla Nakharin University Pattani South Thailand. As such, this review will be an important guide and reference for colleges, Islamic college centers and institutions of Islamic universities in Thailand and especially the Islamic College of Islamic University of Songkla Nakharin University Pattani campus, Thailand.